Effect of Zero, Strip and Conventional Till System on Performance of Wheat - Chaudhary, V P; Singh, Bachchan (Journal of Agricultural Engineering, 2002)
The study on zero, strip and conventional till systems was conducted to compare their performance of sowing wheat. Randomized block design was used for conducting the experiments. The results indicated that zero till system saved fuel and time as compared to strip and conventional systems. The saving in irrigation for zero till was 34 and 47% over strip till and conventional systems. The grain yields were 3627, 3637 and 3488 kg/ ha for zero, strip and conventional till systems, respectively.